Synthesis of schiff base from dialdehyde breadfruit (Artocarpus altilis) starch and aniline with antibacterial properties - Cut Fatimah Zuhra; Rianto Damanik (Universitas Syiah Kuala, 2025)
Schiff bases were successfully synthesized via a condensation reaction between dialdehyde starch (DAS), derived from breadfruit (Artocarpus altilis) starch, and aniline. DAS was prepared through oxidative cleavage of the vicinal diol groups in native starch using sodium periodate. The formation of DAS was confirmed qualitatively by the appearance of a brick-red precipitate upon addition of Fehlings reagent and a marked increase in its water solubility. Fourier Transform Infrared (FT-IR) spectroscopy revealed a strong absorption band at 1635.64 cm, corresponding to the aldehyde C=O stretching vibration, supporting the successful oxidation. The oxidized starch showed a high degree of oxidation (80.9%) and a carbonyl content of 10.36%. Condensation between the aldehyde groups of DAS and the amino group of aniline resulted in the formation of a Schiff base. FT-IR analysis of the resulting compound revealed absorption bands at 1635.64 cm and 1604.77 cm, indicating the formation of imine (-C=N-) bonds, while a peak at 871.82 cm confirmed the presence of aromatic ring structures. The antibacterial activity of the synthesized Schiff base was evaluated using the disk diffusion method, showing strong inhibitory effects against Escherichia coli and Staphylococcus aureus. These findings showed that starch-based Schiff bases represent a promising class of biodegradable antibacterial agents with potential applications in biomedicine and biomaterials.